Pengambilan Keputusan Majelis Hakim Dalam Perkara Perceraian Di Pengadilan Agama Kabupaten Sidrap - Makmur, Makmur; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to analyze and describe the decision making of the panel of judges in divorce cases in the religious court of Sidrap Regency. This study used a case study with qualitative research. The research data were collected through observation, interviews, documentation. Data validation was carried out by source trigulation, techniques, and then analyzed through data reduction, data presentation, and conclusions. The results showed that the decision making of the panel of judges in divorce cases in the religious court of Sidrap district was based on 3 (three) indicators, namely the intelligence stage was  in accordance with the systematics of the trial in making decisions of the Panel of Judges in divorce cases in the Religious Court of Sidrap Regency, then the design stage was completed. In accordance with the identification steps and in the formulation of problem solving related to divorce cases and the election stage, there were two alternative choices of decisions, namely the accepted or not accepted options, but there were still the plaintiffs or defendants who objected to the decision of the panel of judges Keywords: Decision Making, Panel of Judges, Divorce Case